The Electrochemical Behavior of Au/AuNPs/PNA/ZnSe-QD/ACA Electrode Towards CySH Oxidation - Azadbakht, Azadeh; Abbasi, Amir Reza; Derikvand, Zohreh; Karimi, Ziba (Nano-Micro Letters, 2015)
This work describes the electrochemical behavior of azodicarboxamide (ACA) film immobilized on the surface of penicillamine (PNA)/ZnSe-quantum dot (ZnSe-QD) gold nanoparticle (AuNPs) Au electrode. Electrocatalytic activity of modified electrode toward the oxidation of cysteine (CySH) was investigated. The surface structure and composition of the sensor were characterized by scanning electron microscopy (SEM). Oxidation of CySH on the surface of modified electrode was investigated with cyclic voltammetry, electrochemical impedance spectroscopy (EIS), hydrodynamic voltammetry and chronoamperometry methods. The results show that the PNA/ZnSe-QD/ACA film displays excellent electrochemical catalytic activities towards CySH oxidation. The modified electrode shows reproducible behavior and high level of stability during the electrochemical experiments. Also it has short response time, low detection limit, high sensitivity and low operation potential, which can be used as an amperometric sensor for monitoring of CySH. The proposed modified electrode was successfully used for determination of CySH in real sample such as human serum.